To study the defects in an ingot made of wax and naphthalene mixture - Rao, Lakkoju Sankara (Main Library, IIT (BHU), Varanasi, 2022)
This video shows the preparation Ingot mould, melting and pouring of wax, Ingot examination, finding the pipe volume, taking the impression of pipe. PART 1 Introduction PART 2 Ingot Melting and Pouring PART 3 Procedure PART 4 Pipe Volume PART 5 Cutting & seeing pipe PART 6 Impression and Results
Keywords: Ingot